2017
DOI: 10.21315/eimj2017.9.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Trends of Use of Social Media by Medical Students

Abstract: Introduction: As the online environment has evolved, the use of social networking sites (SNSs) has been integrated into the methods of teaching. Students across the world are currently using SNSs to enhance their learning. Objective: This study sought to explore the students' use of social media, in particular that of Facebook groups in medical education at the University of Ottawa. Methods: Pre-clerkship medical students (n = 160) were surveyed regarding the trends of use of SNSs in their learning. The survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Educators used them to share resources, establish a dialogue with students, and facilitate classroom activities. Students used them for informal conversation, for accessing and sharing educational resources, to arrange educational and social events, to discuss opinions, and to participate in surveys, quizzes and educational games 90,109,110,113 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educators used them to share resources, establish a dialogue with students, and facilitate classroom activities. Students used them for informal conversation, for accessing and sharing educational resources, to arrange educational and social events, to discuss opinions, and to participate in surveys, quizzes and educational games 90,109,110,113 …”
Section: Resultsmentioning
confidence: 99%
“…Students used them for informal conversation, for accessing and sharing educational resources, to arrange educational and social events, to discuss opinions, and to participate in surveys, quizzes and educational games. 90,109,110,113 Several studies delivered structured teaching using social media platforms. 6,36,48,65,85 Use of social media within structured learning activities was found to improve communication and participation, 82,88 and facilitate teamwork.…”
Section: Educational Activitymentioning
confidence: 99%
“…Increased use of the internet via laptops, smartphones, tablets and other handheld devices, along with cheaper data services, make internet use more widespread. Some studies found that students using social media to communicate with their colleagues and for learning, and many students rely on social media to access the knowledge in a free and easy way (43).…”
Section: Discussionmentioning
confidence: 99%
“…Social media has become an important information dissemination tool for health care organizations. Today nearly 70% of US adults use social media platforms (Pew Research Center 2018), such as Facebook, Twitter, LinkedIn, Reddit, and online message boards, to access, generate, and share content (Kind et al 2010;George et al 2013; Korda and Itani 2013;Fung et al 2015;Callum Staff et al 2016;El Bialy and Ayoub 2017). As a result, these platforms provide health care organizations with easy access to a public eager to use the Internet in its medical decision making-an eagerness demonstrated by the fact that 80% of all US adult Internet users search online for health information (Fox 2011) and these users often receive medical opinions from the web before they consult a physician (Gualtieri 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The health care community's embrace of social media has resulted in a variety of success stories: social media has proven effective at connecting organ donors with transplant candidates (Henderson 2018), offering anxietyrelieving support to patients (Attai et al 2015), and facilitating learning among medical students (El Bialy and Ayoub 2017). Social media has also been shown to have a positive influence on people's health (Maher et al 2014;Laranjo et al 2015), successfully encouraging the adoption of such behaviors as increased physical activity (Valle et al 2013), improved weight loss among the obese (Turner-McGrievy and Tate 2013), and responsible resource use during emergencies (Jones 2011).…”
Section: Introductionmentioning
confidence: 99%